2013
DOI: 10.3136/fstr.19.675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhomogeneous Spatial Distribution of Aroma Compounds on Perceived Aroma Intensity and Human Eating Behavior for Neutral pH Gels

Abstract: Effects of inhomogeneous spatial distribution of aroma compounds were investigated on the perceived aroma intensity and human eating behavior using polysaccharide gels as a food model. Gels tested were structured using gel-in-gel configuration to create different degrees of inhomogeneous spatial aroma distribution, and their pH values were set at neutral (6.7 − 6.8). There were no differences in mechanical properties between the structured gels. A greater degree of inhomogeneous spatial aroma distribution incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The diffusion issue could explain the difference between our results and those reported by others, which showed that heterogeneity of the spatial aroma distribution in gels increased perceived aroma intensity. 27,28 Nevertheless, added ham aroma significantly contributed to enhanced saltiness regardless of its spatial distribution (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The diffusion issue could explain the difference between our results and those reported by others, which showed that heterogeneity of the spatial aroma distribution in gels increased perceived aroma intensity. 27,28 Nevertheless, added ham aroma significantly contributed to enhanced saltiness regardless of its spatial distribution (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%
“…26 Moreover, it is noteworthy that similar observations were reported on aroma perception for a heterogeneous distribution of volatile compounds in gels. 27,28 Another strategy currently under investigation to compensate for sensory loss in low-salt food proposes to take advan-tage of the cross-modal interactions between odour and taste to enhance taste intensity. [29][30][31] The perception of flavour is hence a multisensory process involving the integration of taste and odour as a function of their congruency, relying on consumers' previous food experiences, memory or culture.…”
Section: Introductionmentioning
confidence: 99%
“…The agar-gelatin gels with low fracture strain, absorbed minimal amounts of saliva, indicating that the gels of high fragility did not require the extra saliva lubrication for safe swallowing [72]. The saliva content was higher in gels, which were processed for longer time in the oral cavity due to the inhomogeneous spatial distribution of aroma compounds in the gels, despite the similar mechanical properties of the gels [79,80]. The saliva hydration of the bolus also depends on the initial water content and composition of the food.…”
Section: Salivary Capacities-hydrationmentioning
confidence: 99%
“…This principle has been extended to layered gels alternating between low and rich domains of tastants. It has been shown that heterogeneous distributions of sugar [ 16 ], salt [ 17 ], fat [ 18 ], and odourants [ 19 , 20 ] increase perception intensity. Similar observations were reported in more complex foods for saltiness perception: bread [ 21 ], cream-based foods [ 22 ], and beef frankfurter [ 23 ], allowing a significant reduction in sodium content.…”
Section: Introductionmentioning
confidence: 99%